The toxic and environmental evaluation of pyrolytic liquids byAllium cepatest - Pekol, Sefa; Caglar, Atila; Aydinli, Bahattin (Informa UK Limited, 2012)
In this study, liquid products obtained from the pyrolysis of hazelnut shell (HS), with and without ultra-high molecular weight polyethylene (UHMWPE), were subjected to the Allium cepa test system. Pyrolysis in conjunction with the A. cepa test is a promising technology not only from the perspective of energy savings and a source of precious material, but in terms of the removal of hazardous material from the environment in safe manner. Dosages of pyrolytic liquids dissolved in water were determined according to lethal dose (LD50), with three different solution concentrations. The preparates were dyed with acetocarmine. The mitotic index decreased and chromosomal aberration, especially stickiness and c-mitosis, increased with dosage and time. The addition of UHMWPE to HS in the pyrolysis process resulted in less harmful chemical agents, as observed by the relatively higher mitotic index and lower levels of chromosomal aberration.
Keywords: 6. Clean water